Prognostic Value of Thyroid Hormone Ratio in Patients With Advanced Metastatic Renal Cell Carcinoma: Results From the Threefour Study (Meet-URO 14) - Maruzzo, Marco; Verzoni, Elena; Vitale, Maria Giuseppa; Dionese, Michele; Buti, Sebastiano; Galli, Luca; Zivi, Andrea; Watutantrige-Fernando, Sara; Zielli, Teresa; Zanardi, Elisa; Sabbatini, Roberto; Basso, Umberto; et al. (Frontiers in Oncology, 2021)
Background Thyroid hormone impairment, represented as an alteration in levels of thyroid hormones and a lower fT3/fT4 ratio, has been correlated with a worse prognosis for both cancer and non-cancer patients. The role of baseline thyroid function in patients with metastatic renal cell carcinoma (mRCC) however, has not been studied yet. Materials and Methods We recorded clinical data, baseline biochemical results, and oncological outcomes from 10 Oncology Units in Italy. We stratified patients into three groups according to the fT3/fT4 ratio value and subsequently analyzed differences in progression-free survival (PFS) and overall survival (OS) in the three groups. We also performed univariate and multivariate analyses to find prognostic factors for PFS and OS. Results We analyzed 134 patients treated with systemic treatment for mRCC. Median PFS in the low, intermediate, and high fT3/fT4 ratio group were 7.5, 12.1, and 21.7 months respectively (p<0.001); median OS in the three groups were 36.5, 48.6, and 70.5 months respectively (p =0.006). The low fT3/fT4 ratio maintained its prognostic role at the multivariate analysis independently from IMDC and other well-established prognostic factors. The development of iatrogenic hypothyroidism was not associated with a better outcome. Conclusion We found that baseline thyroid hormone impairment, represented by a low fT3/fT4 ratio, is a strong prognostic factor in patients treated for mRCC in first line setting and is independent of other parameters currently used in clinical practice.